G-quadruplex formation in RNA aptamers selected for binding to HIV-1 capsid - Mayer, Miles D.; Lange, Margaret J. (Frontiers in Chemistry, 2024)
HIV-1 capsid protein (CA) is essential for viral replication and interacts with numerous host factors to facilitate successful infection. Thus, CA is an integral target for the study of virus-host dynamics and therapeutic development. The multifaceted functions of CA stem from the ability of CA to assemble into distinct structural components that come together to form the mature capsid core. Each structural component, including monomers, pentamers, and hexamers, presents a variety of solvent-accessible surfaces. However, the structure-function relationships of these components that facilitate replication and virus-host interactions have yet to be fully elucidated. A major challenge is the genetic fragility of CA, which precludes the use of many common methods. To overcome these constraints, we identified CA-targeting aptamers with binding specificity for either the mature CA hexamer lattice alone or both the CA hexamer lattice and soluble CA hexamer. To enable utilization of these aptamers as molecular tools for the study of CA structure-function relationships in cells, understanding the higher-order structures of these aptamers is required. While our initial work on a subset of aptamers included predictive and qualitative biochemical characterizations that provided insight into aptamer secondary structures, these approaches were insufficient for determining more complex non-canonical architectures. Here, we further clarify aptamer structural motifs using focused, quantitative biophysical approaches, primarily through the use of multi-effective spectroscopic methods and thermodynamic analyses. Aptamer L15.20.1 displayed particularly strong, unambiguous indications of stable RNA Gquadruplex (rG4) formation under physiological conditions in a region of the aptamer also previously shown to be necessary for CA-aptamer interactions. Non-canonical structures, such as the rG4, have distinct chemical signatures and interfaces that may support downstream applications without the need for complex modifications or labels that may negatively affect aptamer folding. Thus, aptamer representative L15.20.1, containing a putative rG4 in a region likely required for aptamer binding to CA with probable function under cellular conditions, may be a particularly useful tool for the study of HIV-1 CA.